Demographic development in Czechoslovakia in 1979 - Srb, V (Demosta, 1980)
The author presents a brief review of demographic development in Czechoslovakia in 1979. He analyzes trends in nuptiality, fertility, mortality, divorce, abortion, and migration and examines the effects of various socioeconomic factors on these trends
Keywords: Economics; Population Dynamics; socioekonomické faktory; Czechoslovakia; statistika jako téma; populační dynamika; populační růst; výzkum; Eastern Europe; Economic Factors; Population; Europe, Eastern; Population Growth Estimation; Population Growth--changes; Developed Countries; Europe; východní Evropa; Population Growth; Československo; demografie; Statistics as Topic; Demography; Estimation Technics; vyspělé země; Research Methodology; populace; Demographic Factors; Socioeconomic Factors; ekonomika; Research; Evropa